Teologi Muhammad ‘Abduh: Kajian Kitab Risâlat al-Tawhîd - Ismail, Hadi (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2012)
This article discusses the renewal of of Islamic theology proposed by Muhammad ?Abduh in the modern era, especially in his work Risâlat al-Tawhîd. In this case, ?Abduh provided the highest position of reason in interpreting al-Qur?ân. In fact, if there is a contradiction between reason against revelation, the revelation should be interpreted in accordance with the provisions of reason. In addition, by criticizing the fatalistic theology of Jabarîyah, ?Abduh gave the humans freedom to do anything according to their will. This is because by using their mind (reason), humans are able to consider the act they were doing along with their consequences, to make decisions based on their own will, and to realize their deeds based on their own resources. However, ?Abduh emphasized that such freedom is not an absolute freedom.